Malawi : Poverty Reduction Strategy Paper; Third Annual Progress Report; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The government of Malawi has finalized its third annual progress report (APR) of Malawi's Poverty Reduction Strategy (MPRS) for the period July 2004 to December 2005. The government's strategy as described in the MPRS focuses on reducing poverty through creating a stable macroeconomic environment and undertaking activities in four interrelated pillars. IMF staff recommends that in future processes, extra effort is made to ensure greater participation by the private sector and key members of parliament. The food security crisis was deeper than anticipated, leading to higher expenditures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Malawi